2002
DOI: 10.1046/j.1440-1827.2002.01369.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of MUC5AC in colorectal carcinoma and relationship with prognosis

Abstract: Overexpression and alterations in the glycosylation of gastric mucins have been described in colorectal carcinoma. The purpose of our study was to confirm aberrant expression of MUC5AC in colorectal carcinoma, to investigate relationships between clinicopathological parameters and MUC5AC expression, and to determine if MUC5AC expression may be a prognostic factor for colorectal carcinoma. Immunohistochemical staining using an antibody against MUC5AC tandem repeat epitopes was performed on colorectal tumor spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
56
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 28 publications
7
56
1
Order By: Relevance
“…1 and Table I). Similarly, other studies have shown that MUC5AC is not detected in the normal colon, but is frequently found in adenomas and carcinomas (18,(30)(31)(32). Other prior studies reported that an increase in expression of MUC5AC was observed in sporadic cancer with high microsatellite instability (33) and that MUC5AC expression in intrahepatic cholangiocarcinoma was found to be an independent prognostic factor by multivariate survival analysis (34).…”
Section: N ----------------------------------------------------------mentioning
confidence: 79%
See 1 more Smart Citation
“…1 and Table I). Similarly, other studies have shown that MUC5AC is not detected in the normal colon, but is frequently found in adenomas and carcinomas (18,(30)(31)(32). Other prior studies reported that an increase in expression of MUC5AC was observed in sporadic cancer with high microsatellite instability (33) and that MUC5AC expression in intrahepatic cholangiocarcinoma was found to be an independent prognostic factor by multivariate survival analysis (34).…”
Section: N ----------------------------------------------------------mentioning
confidence: 79%
“…Other prior studies reported that an increase in expression of MUC5AC was observed in sporadic cancer with high microsatellite instability (33) and that MUC5AC expression in intrahepatic cholangiocarcinoma was found to be an independent prognostic factor by multivariate survival analysis (34). The presence of MUC2 and/or MUC5AC in colorectal mucinous adenocarcinoma has been shown to be associated with proximal (right-sided) CRC location (32,33). There was no statistically significant association between gender and expression of MUC2 and/or MUC5 in the present study.…”
Section: N ----------------------------------------------------------mentioning
confidence: 94%
“…MUC5AC is expressed in adenoma and conventional adenocarcinoma with well to moderate differentiation in the colon and rectum [16][17][18][19][20] . In addition, MUC5AC has also been reported to be expressed in 56%-63% cases of colorectal MAC [17,18] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, MUC5AC has also been reported to be expressed in 56%-63% cases of colorectal MAC [17,18] . On the other hand, Kocer et al [19] have reported that the absence of MUC5AC expression in tumors can be a prognostic factor for more aggressive adenocarcinoma in the colon and rectum. In this study, we found that the frequency of MUC5AC/CHL2 expression was significantly lower in high-grade MAC compared with low-grade MAC.…”
Section: Discussionmentioning
confidence: 99%
“…MUC1 expression is low in mucinous tumours but in those tumours that show overexpression, there is an association with worse prognosis and chemoresistivity to certain chemotherapy agents [51]. Conversely, the MUC5 gene has been shown to confer a survival benefit [52] and unusually is overexpressed in some mucinous tumours. However, MUC5 also shows a greater association with proximal location of the colorectum, which may explain the poor prognosis of mucinous rectal cancer; that this may be due to relative underexpression of MUC5.…”
Section: Radiological Diagnosis and Measuring Responsementioning
confidence: 99%